Anāgatavaṃsa desanā = The sermon of the chronicle-to-be - Măddēgama, Udaya Praśānta.; Kassapatthēra active 1160-1230.; Holt, John 1948- (Delhi Motilal Banarsidass Publishers, 1993)
Free prose transaltion of Anāgatavaṃsa desanā, an adaptation of the Anāgatavaṃsa by Kassapathēra, fl. 1160-1230, on the story of Maitreya, Buddhist deity.
Includes bibliographical references (pages 17-18) and index.
Keywords: Maitreyanātha.